Budget impact of everolimus for the treatment of progressive, well-differentiated, non-functional neuroendocrine tumors of gastrointestinal or lung origin that are advanced or metastatic. (3rd April 2017) - Rose, Darya B.; Nellesen, Dave; Neary, Maureen P.; Cai, Beilei
Abstract: Background: Advanced neuroendocrine tumors (NETs) are a rare malignancy with considerable need for effective therapies. Everolimus is a mammalian target of rapamycin (mTOR) inhibitor approved by the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) in 2016 for treatment of adults with progressive, well-differentiated, non-functional NETs of gastrointestinal (GI) or lung origin that are unresectable, locally advanced, or metastatic. Objective: To assess the 3-year budget impact for a typical US health plan following availability of everolimus for treatment of GI and lung NETs. Methods An economic model was developed that considered two perspectives: an entire health plan and a pharmacy budget. The total budget impact included costs of drug therapies, administration, hospitalizations, physician visits, monitoring, and adverse events (AEs). The pharmacy model only considered drug costs. Results: In a US health plan with 1 million members, the model estimated 66 patients with well-differentiated, non-functional, and advanced or metastatic GI NETs and 20 with lung NETs undergoing treatment each year. Total budget impact in the first through third year after FDA approval ranged from $0.0568–$0.1443 per member per month (PMPM) for GI NETs and from $0.0181–$0.0355 PMPM for lung NETs. The total budget impact was lower than the pharmacy budget impact because it included cost offsets from administration and AE management for everolimus compared with alternative therapies (e.g. chemotherapies). Limitations: Because GI and lung NETs are rare diseases with limited published data, several assumptions were made that may influence interpretation of results. Conclusions: The budget impact for everolimus was minimal in this rare disease area with a high unmet need, largely due to low disease prevalence. These results should be considered in the context of significant clinical benefits potentially provided by everolimus, including significantly longer progression-free survival (PFS) for advanced GI and lung NET patients.